Reflection, Resistance, and Reconstruction: Professional Identity Development Among Basic-Level Nepali Female English Teachers - Oli, Pampha; Kandel, Rajan Kumar (GS Spark: Journal of Applied Academic Discourse, 2025)
The professional identity of English language teachers is crucial to their instructional effectiveness, self-perception, and students' target language learning. This study explores the perceptions of basic-level English language female teachers on their identity construction in Nepal. Under a qualitative approach that employed a narrative inquiry design, five female teachers from Birendranagar Municipality participated in the study. Data were collected through in-depth interviews and participants’ reflective journals. It showed that teachers’ identity construction was influenced by socio-cultural norms and institutional contexts. Female English teachers actively shaped their professional identities through reflection, resistance, and reconstructive engagements. Findings suggest the need for supportive institutional environments and gender-sensitive policies to enhance English language female teachers’ identity construction in English as a foreign language context. This study contributes to a broader understanding of how gender, language teaching, and socio-cultural norms intersect to shape professional identity within the Nepali context through interpretative and socio-cultural lenses.